Monetary policy, bank lending, and inflation in the post-pandemic recovery era: A case of the East African Community - Ronald Ochen (Kenya Bankers Association (KBA), 2024)
This paper investigates the underlying dynamic relationships between monetary policy, bank lending, and inflation during the post-pandemic recovery era in the East African Community. To achieve this, I analysed monthly macroeconomic data on central bank rates, consumer price index, lending interest rates, commercial bank foreign assets, net foreign assets, bank loans, and the US Fed funds rates from January 2021 to June 2023 using a panel Vector Autoregressive model. Empirical results from the East African Community as a bloc and in specific countries indicate that when the central bank rate increases by one standard deviation, there is a decrease in the bank loans available for lending. Additionally, there is a decline in the consumer price index, although it remains positive. Also, a one standard deviation shock in consumer price index leads to a decrease in bank loans in first periods but later, bank loans pick up and gain a positive stance while central bank rates remain positive throughout the 12 periods. Conversely, commercial bank lending interest rates increase when the central bank rate increases by one standard deviation. Moreover, when the US Fed funds rate increases by one standard deviation, there is a decrease in commercial bank foreign assets (loans and deposits), but an increase in the central bank rate and lending interest rates. These findings emphasize that the bank lending channel of transmission of monetary in EAC is susceptible to domestic and external shocks thus commercial bank's capacity to create credit is compromised in response to a tight monetary policy stance.
Keywords: 330; Monetary Policy; Bank Lending; Inflation; Post-Pandemic Recovery Era; PVAR; East African Community